ANALISIS HUBUNGAN ATRIBUT EKOLOGI LAMUN DENGAN KUALITAS PERAIRAN DI TAMAN NASIONAL BALURAN KABUPATEN SITUBONDO - Sutadi Sutadi; Lilik Sulistyowati; Eko Sriwiyono (Sekolah Menengah Kejuruan (SMK) Pustek, 2021)
Seagrass is one of the important ecosystems in coastal but it’s prone to damage by humans or natural factors. The existence of human activities, pollution and tourism activities in the coastal of Baluran National Park are factors that allow disruption of growth and changes of seagrass ecosystem. The study was conducted in May - June 2020 in order to identify the diversity of seagrass species, density, cover and correlations of seagrass attributes with the water quality in the Baluran National Park. (diversity, equitability and dominance) and the research was conducted at 6 stations. Seagrass observations using the